EDUKASI KEAMANAN SIBER BAGI REMAJA SEKOLAH MENENGAH DALAM MENGHADAPI ANCAMAN HOAKS DAN CYBERBULLYING - Rahmawati; Abdul Rahman; Muhammad Nur Iman (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study aims to enhance cybersecurity awareness among secondary school students through an educational program focused on the prevention of hoaxes and cyberbullying. The initiative was implemented in response to the growing exposure of adolescents to misinformation, online harassment, and privacy risks in digital environments. Using a participatory approach, the program involved 50 students from two secondary schools who participated in workshops, simulations, and interactive discussions. Data were collected through pre-test and post-test questionnaires, observations, and semi-structured interviews to assess knowledge, attitudes, and behavioral changes. The results revealed a significant improvement in participants’ understanding of online safety concepts, including critical evaluation of digital information, ethical communication, and privacy management. Statistical analysis using a paired sample t-test (p < 0.05) indicated an increase in cybersecurity literacy after the intervention. Qualitative findings supported this, showing enhanced awareness, empathy, and responsibility in digital interactions. Overall, the program successfully empowered students to identify and respond effectively to hoaxes and cyberbullying, fostering a safer and more ethical online culture among youth. These findings highlight the importance of continuous cybersecurity education in schools as a strategic effort to build digital resilience and promote responsible digital citizenship.